Fun with Integration

Calculus Level 2

0 1 ( 1 x 2 ) 9 x 9 d x \int_0^1 \left(1-x^2\right)^9 x^9 \, dx

Let I I denote the value of the integral above. What is the sum of digits of I 1 ? I^{-1}?


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Tanishq Varshney
Jul 25, 2015

let t = x 2 t=x^2

d t = 2 x d x dt=2x dx

0 1 1 2 ( 1 t ) 9 t 4 d t \large{\displaystyle \int^{1}_{0} \frac{1}{2}(1-t)^{9}t^4dt}

using beta function

0 1 ( 1 t ) x 1 t y 1 = ( x 1 ) ! ( y 1 ) ! ( x + y 1 ) ! \large{\displaystyle \int^{1}_{0} (1-t)^{x-1}t^{y-1}=\frac{(x-1)! (y-1)!}{(x+y-1)!}}

I = 1 2 × 9 ! × 4 ! 14 ! I=\frac{1}{2} \times \frac{9! \times 4!}{14! }

I 1 = 20020 I^{-1}=20020

i miscalculated twice and the third time when i got the right answer i missed that the answer entered should be sum of digits of the inverse of I . silly me.

Anurag Pandey - 3 years ago
Aritra Kundu
Jul 25, 2015

Moderator note:

You don't need to use trigonometric substitution. A better substitution to use is y = 1 x 2 y = 1-x^2 or y = x 2 y=x^2 . Do you see why?

And there's a simpler approach afterwards too. Are you familiar with Beta functions?

0 1 x m ( 1 x ) n d x = m ! n ! ( m + n + 1 ) ! \int_0^1 x^m (1-x)^n \, dx = \frac{m! \ n!}{(m+n+1)!}

I am not familiar with beta function right now. So, I did it by substitution.

Aritra Kundu - 5 years, 10 months ago

Beta Functions?

Jun Arro Estrella - 5 years, 10 months ago

And both substn and beta fn require calculation

Swapnil Vatsal - 3 years, 11 months ago

Use Wallis Formula

Kailash Agrawal - 3 years, 9 months ago

Trigonometry substitution is lengthy

Roy Satyam - 3 years, 6 months ago

At least I know how to do this by trig substitution rather than some fancy beta function

Yinchen Wu - 3 years, 5 months ago

You can use the trigonometric representation of the beta function. That makes it really easy.

N. Aadhaar Murty - 9 months, 3 weeks ago
Laurent Shorts
Mar 31, 2016

We have: 0 1 x n ( 1 x 2 ) m d x {\displaystyle \int_{0}^{1}}x^{n}(1-x^{2})^{m}\mathrm{d}x = ( x n + 1 n + 1 ( 1 x 2 ) m ) 0 1 = 0 0 1 x n + 1 n + 1 m ( 1 x 2 ) m 1 ( 2 x ) d x \,\,\,=\,\,\,\underset{=0}{\underbrace{\biggl(\dfrac{x^{n+1}}{n+1}(1-x^{2})^{m}\biggr)\biggl|_{0}^{1}}}\,\,\,-\,\,\,{\displaystyle \int_{0}^{1}}\dfrac{x^{n+1}}{n+1}m(1-x^{2})^{m-1}(-2x)\mathrm{d}x = 2 m n + 1 0 1 x n + 1 ( 1 x 2 ) m 1 d x ={\displaystyle \dfrac{2m}{n+1}\int_{0}^{1}}x^{n+1}(1-x^{2})^{m-1}\mathrm{d}x

Therefore:

0 1 x 9 ( 1 x 2 ) 9 d x = 18 10 16 12 14 14 2 26 0 1 x 27 d x {\displaystyle \int_{0}^{1}}x^{9}(1-x^{2})^{9}\mathrm{d}x\,\,\,=\,\,\,\dfrac{18}{10}·\dfrac{16}{12}·\dfrac{14}{14}·\ldots·\dfrac{2}{26}\,\,·\,\,{\displaystyle \int_{0}^{1}}x^{27}\mathrm{d}x = 9 8 1 5 6 13 1 28 = 4 3 2 1 10 11 12 13 28 = 1 10 11 13 14 =\dfrac{9·8·\ldots·1}{5·6·\ldots·13}\,·\,\dfrac{1}{28}=\dfrac{4·3·2·1}{10·11·12·13\,·\,28}=\dfrac{1}{10·11·13·14} = 1 2 0 020 =\dfrac{1}{20'020}

I particularly started using Gamma from today, so 0 π / 2 cos m x sin n x d x = Γ ( m + 1 2 ) Γ ( n + 1 2 ) 2 Γ ( m + n + 2 2 ) \int_0^{\pi/2} \cos^m x \sin^n x\, dx = \dfrac{\Gamma\left(\dfrac{m+1}2\right)\Gamma\left(\dfrac{n+1}2\right)}{2\Gamma\left(\dfrac{m+n+2}2\right)}

So, substituting x = sin θ d x = cos θ d θ I = 0 π / 2 cos 19 θ sin 9 θ d θ = Γ ( 20 2 ) Γ ( 10 2 ) 2 Γ ( 30 2 ) I = 9 ! 4 ! 2 14 ! = 1 20020 x = \sin\theta\\dx = \cos \theta ~d\theta\\\ I = \int_0^{\pi/2} \cos^{19} \theta \sin^9 \theta\, d\theta = \dfrac{\Gamma\left(\dfrac{20}2\right)\Gamma\left(\dfrac{10}2\right)}{2\Gamma\left(\dfrac{30}2\right)}\\I = \dfrac{9!\cdot 4!}{2\cdot 14!} = \dfrac1{20020}

Or as an alternative, Beta also helps. Substituting x 2 = t 2 x d x = d t I = 0 1 ( 1 t ) 9 t 4 d t = B ( 10 , 5 ) x^2 = t\\2x~dx = dt\\I = \int_0^1 (1-t)^9 t^4~dt =\mathrm B(10, 5)

And then going back to Gamma, B ( x , y ) = Γ ( x ) Γ ( y ) Γ ( x + y ) \mathrm B(x,y) = \dfrac{\Gamma(x)\Gamma(y)}{\Gamma(x+y)}

So, I = B ( 10 , 5 ) = Γ ( 10 ) Γ ( 5 ) Γ ( 15 ) = 9 ! 4 ! 2 14 ! = 1 20020 I =\mathrm B(10, 5) = \dfrac{\Gamma(10)\Gamma(5)}{\Gamma(15)} = \dfrac{9!\cdot 4!}{2\cdot 14!} = \dfrac1{20020}


Note some important properties: Γ ( x ) = 0 e t t x 1 d t B ( x , y ) = B ( y , x ) = 0 1 t x 1 ( 1 t ) y 1 d t 0 π / 2 cos m x sin n x d x = Γ ( m + 1 2 ) Γ ( n + 1 2 ) 2 Γ ( m + n + 2 2 ) B ( x , y ) = Γ ( x ) Γ ( y ) Γ ( x + y ) Γ ( 1 2 ) = π \Gamma(x) = \int_0^\infty e^{-t} t^{x-1} dt\\\\\mathrm B(x,y) =\mathrm B(y,x) = \int_0^1 t^{x-1}(1-t)^{y-1} dt\\\\ \int_0^{\pi/2} \cos^m x \sin^n x\, dx = \dfrac{\Gamma\left(\dfrac{m+1}2\right)\Gamma\left(\dfrac{n+1}2\right)}{2\Gamma\left(\dfrac{m+n+2}2\right)}\\\\\mathrm B(x,y) = \dfrac{\Gamma(x)\Gamma(y)}{\Gamma(x+y)}\\\\\Gamma\left(\dfrac 12\right) = \sqrt \pi

Shivam Mishra
Feb 24, 2016

'beta' makes it a child's play!!!!

We can directly use Wallis Formula by just plugging in x=Sinz

Kailash Agrawal - 3 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...